Dynamic response of a micro end mill cutter by mode superposition method and study of damping effect on its dynamic performance. (2nd March 2015) - Babu, K. Rajesh; Samuel, G.L.
In the current era of micro/meso mechanical manufacturing (M4) systems, selection of a micro tool plays an important role in executing micromachining operations effectively. Compared with the conventional ultraprecision machine tool the excitation in miniaturised machine tool (MMT) is mainly due to microcutting force. The dynamic response of a MMT must be much more intensive than the ultraprecision machine tool. Hence, study of its dynamic behaviour assumes significance from the viewpoint of obtaining good surface finish and ensuring longer tool life. Furthermore, owing to its smaller size, micro tool fails very frequently and thus the replacement of tool is almost certain in such machining processes. In view of this fact, the present work focuses on estimation of dynamic response of micro end mill cutter by making use of mode superposition method. Also included in this work is the study of effect of damping on its dynamic performance.